Publication Productivity of University of Kerala: A Scientometric View - A. Gopikuttan and Aswathy S (DESIDOC Journal of Library & Information Technology, 2014)
Web of Science is a major citation database which provides access to the world’s leading scholarly literature. University of Kerala is one of the premier higher education institutes which cater the educational needs of the Kerala. The present study evaluates the research productivity of University of Kerala based on the data collected from Web of Science over a period of thirteen years from 2000 to 2012. This study attempts to analyse the overall performance of the faculty members of Science Departments of University of Kerala in research productivity. The parameters such as form-wise, year-wise, subject-wise classification of published papers, most productive authors and the most preferred journals, etc. are considered for the study. The impact factor and the citation received were also analysed. The study reveals that Chemistry is the subject which produces more number of papers while the multi-authorship also possesses a lead role in this subject. Indian journals are the most preferred journals to publish the articles which are followed by UK. Collaborative Coefficient varies from subject to subject. The result shows that the research productivity of the University of Kerala is much recognised at international level.